Pengukuran Kesadaran Keamanan Informasi Dan Privasi Pada Pengguna Smartphone Android Di Indonesia - Akraman, Robbi; Candiwan, Candiwan; Priyadi, Yudi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
Based on statistical data, it is known that Android is the most popular smartphone with the largest number of users in the world, which is about 1.8 billion users. The high number of users also invite the many cases of information security and privacy caused by the lack of awareness of the user such as : spam, spoofing/phising, network incident, malware, uploading something personal data such as photos, phone numbers, addresses or having no antivirus. This study aims to find out about the awareness of the security of information and privacy of Android smartphone users by doing measurement of problem. The awareness has Â some dimensions such as attitude, knowledge and behavior with the seven focus areas of information security namely trust in app repository, misconception about app testing, security and agreement message, pirated application, adoption Security control, spam sms and report of security incidents and three focus areas of privacy are perceived surveillance, perceived intrusion, secondary use of information. This research uses analytical hierarchy process (AHP) to measure the level of awareness of information security and privacy of smartphone users. Overall, the results of the research show that information security has an average level of awareness (71%) but the focus area of report for security incidents has a poor level of awareness (37%) this occur because users prefer to solve their own information security issues experienced and privacy has an average level of awareness (76%). However, for secondary use of information in attitude dimension has low awareness level (66%). Based on the results of this study, it can be concluded that smartphone users in Indonesia have a poor awareness level in maintaining security and privacy of their information.Â